Ethical and Legal Aspects of Telerehabilitation in Saudi Arabia - Ahmed Mushabbab Alhabter; Ahmad Zaheer Qureshi; Sami Ullah (International Journal of Telerehabilitation)
Organizations have their own policies and procedures to govern operational aspects of health care facilities. With the advent of telemedicine, there has been a growing trend in providing telehealth practices without formally exploring the ethical and legislative aspects.  The potential use of electronic and digital services in telerehabilitation can influence various ethical and legal factors, such as confidentiality, consent. and negligence. Thus, establishing clear strategies in this regard is necessary. Ethical and legal aspects of healthcare are influenced by cultural, religious, and legislative rulings of a state. At the same time, the multidimensional scope of rehabilitation in a health system has its own challenges. This narrative review intends to highlight the importance of incorporating the ethical and legislative framework in the telerehabilitation process in Saudi Arabia. A summary of various aspects in-line with unique local attributes is included, which can also help to facilitate regional telerehabilitation services in the Arab World.